Georges Clemenceau and Serbian National Issue - Stojić Radović, Biljana (Napredak, 2025)
This paper examines Georges Clemenceau, a distinguished French statesman, particularly his reflections on Serbia and the Serbian people during the first two decades of the 20th century, especially during the First World War. To provide a comprehensive understanding, we shed light on issues such as Clemenceau’s Balkan policy, his relationship towards the Thessaloniki front, the Yugoslav idea and, consequently, the process that led to Yugoslavia’s international recognition at Versailles. The research has been supported by archival sources and literature from Serbian and French historiographies.
Keywords: Georges Clemenceau; Raymond Poincaré; Nikola Pašić; Annexation Crisis; First World War; Thessaloniki front; Versailles Peace Conference